The Analysis Study of Management, Diagnosis and Surgical Management of De Quervain Tenosynovitis : An Orthopaedic and Traumatology Systematic Review - Supriyadi, Agung; Andimapali, Zulfikar; Fitria, Adina (International Medical Journal Corp. Ltd, 2024)
Background: This systematic review aims to critically evaluate current surgical practices for managing De Quervain's disease and to identify the most effective treatment methods. Methods: This systematic review focused exclusively on full-text articles published in English between 2014 and 2024, following the PRISMA 2020 guidelines to ensure methodological rigor and transparency. Result: The literature search yielded nearly 100 publications from the selected databases. After an initial screening, eight publications were deemed worthy of a more in-depth review. These studies underwent a thorough examination to ensure a comprehensive and rigorous assessment of their findings and methodologies. Conclusion: The review focused on comparing three surgical interventions for De Quervain's disease: longitudinal skin incision, transverse skin incision, and endoscopic release. The results indicated that the longitudinal skin incision may lead to fewer complications, such as nerve injuries, and is associated with improved functional outcomes compared to the other techniques. This suggests that the longitudinal approach could be a preferable option for surgical management of De Quervain's disease.